Implementasi Pendidikan Pancasila Berkebhinekaan Global Sebagai Upaya Menumbuhkan Karakter Literasi Multikuktural Budaya Nusantara Siswa SD - Kusdiani, Silvia Dwi; Tirtoni, Feri (Educatio, 2025)
Abstract Indonesia is a country rich in ethnic, cultural and religious diversity. However, there is still a gap in the understanding and appreciation of differences among the younger generation, which can lead to intolerance and discrimination. Therefore, basic education is crucial in shaping students' characters to appreciate differences. Pancasila education with global diversity can be a means to instill multicultural values that can shape the character of multicultural literacy of Nusantara culture in students. This study aims to determine how the implementation of Pancasila education with global diversity in fostering the character of multicultural literacy of Nusantara culture in elementary school students. The research method used is descriptive qualitative with the research subject being one fourth grade teacher and three fourth grade students of SDN Tambakrejo 2 Krembung in the 2024/2025 school year. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis techniques used include data reduction, data presentation, and conclusion drawing. To test the validity of the data that has been obtained, using triangulation techniques. Based on the results of the study, it shows that the implementation of Pancasila education with global diversity has succeeded in fostering multicultural literacy characters in students. Through teaching Pancasila values and cultural activities such as folklore, traditional clothing competitions, and art performances, students are enthusiastic about learning and appreciating Indonesia's cultural diversity. Although there are obstacles such as difficulties in distinguishing local, national and global cultures, as well as the lack of interactive learning media, with the addition of innovation and more interesting learning resources, students' understanding of Indonesia's cultural diversity can be better. Keywords: Global Diversity, Multicultural Literacy Character, Pancasila Education Abstrak Indonesia adalah negara yang kaya akan keberagaman suku, budaya, dan agama. Namun, masih ada kesenjangan dalam pemahaman dan penghargaan terhadap perbedaan di kalangan generasi muda, yang bisa menyebabkan intoleransi dan diskriminasi. Oleh karena itu, pendidikan dasar sangat penting dalam membentuk karakter siswa agar bisa menghargai perbedaan. Pendidikan Pancasila berkebhinekaan global dapat menjadi sarana untuk menanamkan nilai-nilai multikultural yang dapat membentuk karakter literasi multikultural budaya Nusantara pada siswa. Penelitian ini bertujuan untuk mengetahui bagaimana implementasi pendidikan Pancasila berkebhinekaan global dalam menumbuhkan karakter literasi multikultural budaya Nusantara pada siswa SD. Metode penelitian yang digunakan yaitu kualitatif deskriptif dengan subjek penelitian satu guru kelas IV dan tiga siswa kelas IV SDN Tambakrejo 2 Krembung tahun ajaran 2024/2025. Teknik pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi. Teknik analisis data yang digunakan meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Untuk menguji keabsahan data yang telah diperoleh, menggunakan teknik triangulasi. Berdasarkan hasil penelitian menunjukkan bahwa implementasi pendidikan Pancasila berkebhinekaan global telah berhasil menumbuhkan karakter literasi multikultural pada siswa. Melalui pengajaran nilai-nilai Pancasila dan kegiatan budaya seperti cerita rakyat, lomba pakaian adat, dan pentas seni, siswa antusias mempelajari dan menghargai keberagaman budaya Indonesia. Meskipun ada kendala seperti kesulitan membedakan budaya lokal, nasional, dan global, serta kurangnya media pembelajaran interaktif, dengan penambahan inovasi dan sumber belajar yang lebih menarik, pemahaman siswa tentang keberagaman budaya Indonesia dapat lebih baik. Kata kunci: Berkebhinekaan Global, Karakter Literasi Multikultural, Pendidikan Pancasila